New Choke Ring Design for Eliminating Multipath Effects in the GNSS System - Daming Lin; Encheng Wang; Jie Wang (International Journal of Antennas and Propagation)
An anti-multipath antenna is an antenna that can effectively suppress multipath signals from the source of signal reception. There are many problems in the traditional choke design, such as excessive volume and low elevation gain damage. In this paper, the conventional choke ring is improved by using the complementary trapezoidal structure, and the detailed design process is given. The measured results show that the choke has good resistance to a multipath effect in the navigation frequency band (1.1–1.7 GHz) and can significantly improve the front-to-back ratio of the antenna.